Association Between Depressive Symptoms and Exercise Capacity in Patients With Heart Disease: A META-ANALYSIS. Issue 4 (July 2017) - Papasavvas, Theodoros; Alhashemi, Mohammad; Micklewright, Dominic
Abstract : Purpose: Depression and reduced exercise capacity are risk factors for poor prognosis in patients with heart disease, but the relationship between the 2 is unclear. We assessed the relationship between depressive symptoms and exercise capacity in patients with heart disease. Methods: PubMed, Cochrane Library, Google Scholar, and ProQuest databases were browsed for English-language studies published from January 2000 to September 2013. Studies including adult patients with coronary artery disease, heart failure, congenital heart disease, and implantable cardioverter defibrillator, reporting correlation between a depression scale and exercise capacity ( O2peak, peak watts, estimated metabolic equivalents, and incremental shuttle walk test distance), as well as studies from which such a correlation could be calculated and provided by the authors, were included. Correlation coefficients (CCs) were converted to Fischer z values, and the analysis was performed using a random-effects model. Then, summary effects and 95% CIs were converted back to CCs. Results: Fifty-nine studies (25 733 participants) were included. Depressive symptoms were inversely correlated to exercise capacity (CC = −0.15; 95% CI, −0.17 to −0.12). Heterogeneity was significant ( I 2 = 64%; P < .001). There was no evidence of publication bias (Fail-safe N = 4681; Egger test: P = .06; Kendall test: P = .29). Conclusions: Patients with heart disease and elevated depressive symptoms may tend to have reduced exercise capacity, and vice versa. This finding has clinical and prognostic implications. It also encourages research on the effects of improving depression on exercise capacity, and vice versa. The effects of potential moderators need to be explored. Abstract : Supplemental Digital Content is Available in the Text.We meta-analyzed correlations between depressive symptoms and exercise capacity from 59 studies (25 733 participants) including adult patients with heart disease. Depressive symptoms were inversely correlated to exercise capacity (summary correlation coefficient −0.15; 95% CI, −0.17 to −0.12). Clinical and prognostic implications of this finding are discussed.